A CASE OF SUBCUTANEOUS METASTASIS OF THE ABDOMEN 35 YEARS AFTER SURGERY FOR PAPILLARY CARCINOMA OF THE THYROID - KASUGA, Yoshio; SHIMIZU, Akira; ITO, Tokiko; KOBAYASHI, Motohiro; KUMAKI, Toshinari; AOKI, Takahisa (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2004)
Subcutaneous metastasis of the abdomen from papillary carcinoma of the thyroid is extremely rare. Here we report such a case of a metastatic submucosal tumor at the epigastric region 35 years after surgery for papillary carcinoma of the thyroid in a 73-year-old woman. At the first surgery, a total thyroidectomy with modified neck dissection was carried out because of thyroid cancer. Histological examination showed papillary carcinoma with multiple metastases in the cervical lymph nodes. A 15×15 mm subcutaneous tumor in the epigastric region was found in January, 2003. Aspiration biopsy cytology of the tumor showed papillary carcinoma of the thyroid. There were no cervical lymph node metastases, bone and lung metastasis, so that resection of the tumor was carried out. Histological finding of the tumor showed a poorly differentiated papillary carcinoma. In addition, tissue immunohistochemical staining for thyroglobulin showed positive. We sometimes see clinical cases of hematogenous metastasis of papillary thyroid carcinoma to the tongue, skin, and brain, and this case is also thought to be of rare distant hematogenous metastasis from papillary thyroid carcinoma.